Factors that affect the use of Malaysian e-learning websites by visually impaired users in the transfer of Islamic knowledge - MOHAMMED RAHEEL MOHAMMED ALAHOUL; NURDIANA AZIZAN; NAJWA HAYAATI ALWI (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: The study’s overarching goal is to learn what factors influence VIUs’ adoption of e-Learning platforms and how those platforms are used to impart knowledge. However, the focus of this paper is on the use of e-Learning websites in Malaysia to transfer Islamic knowledge toMethod: This research utilized a qualitative strategy based on in-depth interviews. The survey received responses from 14 very important users (VIUs), 14 knowledge providers (KPs), and 13 service providers (SPs) at 15 different Malaysian institutions and organizations. Results from the survey were analyzed using a thematic approach with an inductive methodology.Findings: Based on the interviews, VIUs came up with four factors that influence how visually impaired people in Malaysia use e-Learning websites to learn about Islam. Social media, user experience, information and communication technology (ICT) infrastructure, government, and non-profit aid play a role.Implications/Novel Contribution: The research presented in this paper can be used to improve Islamic education on e-Learning platforms currently available in Malaysia.